Filsafat Pendidikan Dalam Pengembangan Sains Berbasis Kearifan Lokal - Asrorul Azizi; Rindu Rahmatiah; Muhammad Sarjan; Hamidi Hamidi; Mulia Rasyidi; Muh. Zaini Hasanul Muttaqin; Agus Muliadi; Yusran Khery; Iswari Fauzi; Muhammad Yamin; Bakhtiar Ardiansyah; Sudirman Sudirman (Pusat Riset dan Inovasi Nasional, 2022)
Humans have the ability to think and always try to improve their knowledge. Human nature is naturally full of curiosity so humans are always looking for answers to their curiosity. Humans seek answers to their curiosity through knowledge, and through knowledge will lead to its own satisfaction according to the demands of the times. The knowledge gained is not only knowledge, but is emphasized on knowledge and truth. Learning everything by studying the right scientific foundation is one of the efforts made by humans to obtain the truth. This study aims to determine the nature of the philosophy of education in the development of science based on local wisdom. The surrounding nature gives birth to local wisdom that is unique and is a potential in the development of science. Science or science which includes physics, chemistry, biology using scientific steps, scientific thinking, and using scientific frameworks. This is the beginning of the philosophy of science used to study, uncover, and solve scientific problems for human life. This study discusses the importance of a person in developing science based on local wisdom as a means of maintaining natural resources, culture, customs that exist in people's lives.